2013
DOI: 10.1038/onc.2013.343
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod directly inhibits Hedgehog signalling by stimulating adenosine receptor/protein kinase A-mediated GLI phosphorylation

Abstract: Imiquimod (IMQ), a nucleoside analogue of the imidazoquinoline family, is used in the topical treatment of basal cell carcinoma (BCC) and other skin diseases. It is reported to be a TLR7 and TLR8 agonist and, as such, initiates a Th1 immune response by activating sentinel cells in the vicinity of the tumour. BCC is a hedgehog (HH)-driven malignancy with oncogenic glioma-associated oncogene (GLI) signalling activated in a ligand-independent manner. Here we show that IMQ can also directly repress HH signalling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 70 publications
(92 reference statements)
2
59
1
Order By: Relevance
“…Imiquimod ( Figure 1) is a synthetic nucleoside analog of the imidazoquinoline family, recently approved for topical treatment of small superficial BCCs. This molecule counteracts Hh signaling downstream of SMO by inducing PKA activity ( Figure 2) with consequent GLI2/3 phosphorylation and their cleavage into repressor forms [79]. Other compounds have been identified to impinge the Hh pathway by targeting proteins and/or interactors that modulate GLI factors activity.…”
Section: Pyrviniummentioning
confidence: 98%
“…Imiquimod ( Figure 1) is a synthetic nucleoside analog of the imidazoquinoline family, recently approved for topical treatment of small superficial BCCs. This molecule counteracts Hh signaling downstream of SMO by inducing PKA activity ( Figure 2) with consequent GLI2/3 phosphorylation and their cleavage into repressor forms [79]. Other compounds have been identified to impinge the Hh pathway by targeting proteins and/or interactors that modulate GLI factors activity.…”
Section: Pyrviniummentioning
confidence: 98%
“…Recently Wolff et al showed that imiquimod can directly repress Hh signalling, independently of the TLR/MYD88/NF-kB pathway by negatively modulating Gli activity in BCC and medulloblastoma cells through a mechanism that engages adenosine receptors to control Gli signalling. Pharmacological activation of adenosine receptors with either an adenosine receptor agonist or imiquimod resulted in a PKA-mediated Gli phosphorylation and reduction in Gli activator levels [103]. Makinodan and Marneros demonstrated that PKA activation via the cAMP agonist forskolin is sufficient to completely abolish oncogenic Smo activity in vitro.…”
Section: Itraconazole/arsenic Trioxidementioning
confidence: 98%
“…IMQ is currently in clinical trials in combination with radiation to treat breast cancer metastasis (5x 6Gy; NCT01421017) or glioma (33x 1.8Gy; NCT01400672) (www.clinicaltrials.gov). IMQ’s actions seem multifaceted, sometimes independent of TLRs, namely through redirecting the adenosine receptor-mediated immune suppression to inhibit oncogenic hedgehog signaling and by driving tumor cell death [115, 116]. A TLR4 agonist is being added to RT of sarcoma (NCT02180698) while TLR9 agonists are very promising as adjuvants to the RT of solid and hematological cancers [117, 118].…”
Section: Tlrs In the Context Of Local Tumor Irradiationmentioning
confidence: 99%